Bioactive compounds, antioxidant activity, and mineral content of bróquil: A traditional crop of Brassica oleracea var. italica - Montaner, Celia; Mallor, Cristina; Laguna, Sonia; Zufiaurre, Raquel (Frontiers in Nutrition, 2023)
Brassicaceae edible plants are rich in bioactive compounds and promote health benefits. Hence the interest in expanding knowledge about the brassica cultivars not studied so far. Specifically, underutilized species and local cultivars focus several current research, as they constitute a source of agrodiversity adapted to the territory and with a likely higher content of nutraceutical compounds. In this sense, Bróquil (Brassica oleracea var italica) is a traditional Brassicaceae crop typical of a Spanish region that is grown mainly in family orchards for auto-consumption, but also on small farms for local markets. This work evaluates a collection of thirteen bróquil landraces from the Vegetable Germplasm Bank of CITA (Spain), describing their mineral content, bioactive compounds, and antioxidant activity, including a broccoli commercial variety as control. The study reports data on the health-promoting nutrients and antioxidants in bróquil for the first time. Under our experimental conditions, we found in bróquil a great variability for these compounds that showed on average similar or higher levels than in broccoli control. The different bróquil landraces also revealed variability in both intra and inter accessions, due to the lack of a formal breeding selection. Despite this variability, we can highlight accession HB5. Specifically, we can stand out its antioxidant activity of 87.07±0.81 %I, total phenolic content of 13.21±0.53 mg GAE g-1 dw, total flavonoid content of 14.50±1.29 mg QE g-1 dw, total glucosinolate content of 43.70±1.09 mg SnE g-1 dw, and vitamin C content of 7.21±0.13 mg AA g-1 dw. Regarding bróquil mineral composition, K was the highest macroelement (22.66 to 33.62 mg g-1 dw), followed by Ca, P, and S whose values were relatively lower compared to K. Mg and Na showed the lowest values. Among the microelements evaluated (Mn, Zn, and Fe), iron was the most abundant detected, higher in all bróquil accessions than in broccoli, except for one accession. Therefore, the results reported for bróquil landraces promising nutritional quality. This could lead to an increase in agrobiodiversity and contribute to a more diversified and healthy diet.